An experimental study of elastic properties of dragonfly-like flapping wings for use in biomimetic micro air vehicles (BMAVs) - Sivasankaran, P.N.; Ward, T.A.; Salami, E.; Viyapuri, R.; Fearday, C.J.; Johan, M.R. (Elsevier, 2017)
This article studies the elastic properties of several biomimetic micro air vehicle (BMAV) wings that are based on a dragonfly wing. BMAVs are a new class of unmanned micro-sized air vehicles that mimic the flapping wing motion of flying biological organisms (e.g., insects, birds, and bats). Three structurally identical wings were fabricated using different materials: acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), and acrylic. Simplified wing frame structures were fabricated from these materials and then a nanocomposite film was adhered to them which mimics the membrane of an actual dragonfly. These wings were then attached to an electromagnetic actuator and passively flapped at frequencies of 10–250 Hz. A three-dimensional high frame rate imaging system was used to capture the flapping motions of these wings at a resolution of 320 pixels × 240 pixels and 35000 frames per second. The maximum bending angle, maximum wing tip deflection, maximum wing tip twist angle, and wing tip twist speed of each wing were measured and compared to each other and the actual dragonfly wing. The results show that the ABS wing has considerable flexibility in the chordwise direction, whereas the PLA and acrylic wings show better conformity to an actual dragonfly wing in the spanwise direction. Past studies have shown that the aerodynamic performance of a BMAV flapping wing is enhanced if its chordwise flexibility is increased and its spanwise flexibility is reduced. Therefore, the ABS wing (fabricated using a 3D printer) shows the most promising results for future applications.